In Lieu of Ideology : An Intellectual Biography of Goh Keng Swee - Ooi, Kee Beng (Book collections on Project MUSE., 2010)
Born in Malacca in 1918, Dr Goh Keng Swee reached maturity at a time when European colonialism was breathing its last. By the time this keen-eyed Malayan became self-governing Singapore's first Minister of Finance in 1959, he had made a name for himself as the colony's foremost social scientist, having carried out groundbreaking surveys on urban poverty and housing. He immediately initiated pioneering projects that laid the ground for the island's economic success.